Respuesta :
The equation can be written in vertex form as
y = a(x +2)² - 3
Substituting the given values, we can find the coefficient "a".
-5 = a(-1+2)² -3
-2 = a . . . . . . . . . add 3 and simplify
The coefficient of the squared term is -2.
y = a(x +2)² - 3
Substituting the given values, we can find the coefficient "a".
-5 = a(-1+2)² -3
-2 = a . . . . . . . . . add 3 and simplify
The coefficient of the squared term is -2.
![Ver imagen sqdancefan](https://us-static.z-dn.net/files/d29/40b2f1a76480c9d33801a3adb8fc32fe.jpeg)
Answer:
-2
Step-by-step explanation:
just did it on a p e x